From Enchantment to Disillusion: A Narrative Exploration of Cannabis Use Disorder Among Young Israeli Combat Veterans - Serebro, Miri; Sobol-Goldberg, Shira; Feingold, Daniel (Frontiers in Psychiatry, 2021)
Introduction: Substance use is common among military personnel and war veterans, especially combat veterans. Despite substantially high prevalence of cannabis use and Cannabis Use Disorder (CUD) consistently reported among veterans, little is known about psychological factors which may underlie CUD among this population. Methods: In this study, we used narrative analysis in order to interpret retrospective in-depth interviews of combat veterans (N=12) who were released from mandatory military duty during the past five years and currently qualified for a diagnosis of CUD. Participants were recruited from a larger quantitative study were eligible for participation if they screened positive for a diagnosis of CUD according to the Cannabis Use Disorder Identification Test- Revised (CUDIT-R) questionnaire. CUD diagnosis was validated in-person using the cannabis section of the Alcohol Use Disorder and Associated Disabilities Interview Schedule-5 (AUDADIS-5) interview protocol. All interviews were transcribed and coded using the content analysis procedure. Findings: Five main themes were extracted: (a) Traumatic events (b) Attitudes towards cannabis use (c) Combatant identity (d) The role of authority/father figures, and (e) Moral crisis. A meta-theme has been identified, 'from enchantment to disillusion', representing a gradual psychological shift from a hopeful, highly motivated stance into the current state of mental rupture and moral injury, which are unsuccessfully compensated by excessive use of cannabis. Conclusions: This study shed light on the etiology of CUD among young combat veterans, highlighting the role of supposed self-medication for trauma and sense of betrayal.